A hybrid DEA-MOLP model for public school assessment and closure decision in the City of Philadelphia - Tavana, Madjid; Ebrahimnejad, Ali; Santos-Arteaga, Francisco J.; Mansourzadeh, Seyed Mehdi; Matin, Reza Kazemi (Socio-economic planning sciences, 2018)
Data envelopment analysis (DEA) is generally used to evaluate past performance and multi objective linear programming (MOLP) is often used to plan for future performance goals. In this study, we establish an equivalence relationship between MOLP problems and combined-oriented DEA models using a direction distance function designed to account for desirable and undesirable inputs and outputs together with uncontrollable variables. This equivalence model can be effectively used to support interactive processes and performance measures designed to establish future performance goals while taking into account the preferences of decision makers (DMs). In particular, it allows DMs to consider different efficiency improvement strategies when subject to budgetary restrictions. The applicability of the proposed method and the efficacy of the procedures and algorithms are demonstrated using a case study where the performance of high schools in the City of Philadelphia is evaluated. •We define an equivalence relationship between MOLP and combined-oriented DEA models.•A direction distance function accounts for desirable, undesirable and uncontrollable factors.•Our model supports performance measures while taking into account the preferences of DMs.•DMs can modify the efficiency improvement strategies when subject to budgetary restrictions.•We use the model to evaluate the performance of high schools in the City of Philadelphia.